A Menial on the Strategic Environmental Assessment (Summary) - M. N. Kopylov; S. M. Kopylov (Московский журнал международного права, 2013)
The article deals with the legal aspects of the strategic environmental assessment (SEA). On the bases of the analysis of the 2003 Kiev Protocol on strategic environmental assessment advantages of this procedure are disclosed if compared with the procedure of environmental impact assessment. The main stages of the procedure of strategic environmental assessment are shown. Peculiarities of transboundary consultations and the importance of monitoring stage are identified. The EU Directive 2001/42/ EC on strategic environmental assessment is analyzed as an example of regional mechanism of strategic environmental assessment. It is concluded that the codification of international legal rules, regulating SEA started in the twenty-first century.